THE FORMATION OF ENTREPRENEURIAL SKILLS IN STUDENTS THROUGH PRACTICAL PERFORMANCE IN FINE ARTS CLUBS IN HIGHER EDUCATIONAL INSTITUTIONS - Rahim Turgunovich Ankabayev (European Science Publishing, 2024)
The article aims to develop entrepreneurial skills through the active participation of students in visual arts in exhibitions and competitions with their creative work, the development of artistic and creative competence necessary for their future activities, as well as practical implementation in their clubs.
Keywords: Future teachers, artistic and creative competence, STEAM education, creative workshop,